Swarm, Evolutionary, and Memetic Computing First International Conference on Swarm, Evolutionary, and Memetic Computing, SEMCCO 2010, Chennai, India, December 16-18, 2010. Proceedings - Panigrahi, Bijaya Ketan.; Das, Swagatam.; Suganthan, Ponnuthurai Nagaratnam.; Dash, Subhransu Sekhar. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the First International Conference on Swarm, Evolutionary, and Memetic Computing, SEMCCO 2010, held in Chennai, India, in December 2010. The 86 revised full papers presented were carefully reviewed and selected from 225 submissions.